PENGARUH PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE PADA KINERJA KEUANGAN LEMBAGA PERKREDITAN DESA KECAMATAN ABIANSEMAL - Sandraningsih, Kadek Budi; Putri, Asri Dwija (E-Jurnal Akuntansi; Vol 11 No 3 (2015), 2015)
Good corporate governance (GCG) is regulations and standards relating to the relationship between management and stakeholders. LPD's success is reflected in the financial performance judged by the level of health. The purpose of this study is to determine the effect of GCG principles of financial performance on the LPD in District Abiansemal Badung regency. The sample used for 34 LPD with 68 respondents. Samples was determined using nonprobability sampling method withasaturatedasamples. The data analysisatechniqueaused is multiple linear regression. Thearesultsaof hypothesisatestin is known that the principles of good corporate governance (transparency, accountability, responsibility, independence, and fairness) positive effect on the financial performance of LPD in District Abiansemal Badung regency
Keywords: transparency, accountability, responsibility, independence, fairness, financial performance